Modifikasi Alat Hisap Jentik “Larvanto-Mobile” Tanpa Menguras Air - Suhermanto Suhermanto; Supriadi Supriadi; Erris Erris (Poltekkes Kemenkes Yogyakarta, 2020)
There were five kecamatans in Jambi City that have not fulfilled the program target of Larva Free Index, i.e. ?95%. The community member is needed to be actively engaged to drain their water containers. Larvanto-mobile is a device modified to catch larvae without draining the water. The aim of the study was to identify the number of Aedes sp larvae that can be caught by the device and to define its operational time. It was a pre-experiment quantitative study with post-test only design. Field observation was conducted on 40 randomly selected houses where larvae were found. The study results show that Larvanto-mobile can catch larvae as much as 12-14 per minute. The most siginificant catching time is in minute I, compared to minute II to minute V. The device can be operasionalized in a single battery recharge for four to six houses, and the ave- rage sucking time is about 11 to 20 minutes per house. For advanced study, in order to solve the lighting problem, it is recommended that Larvanto-mobile is equipped with mini flashlight to maxi- mize its larvae catching ability.